2002
DOI: 10.1182/blood.v99.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Elastic tissue abnormalities resembling pseudoxanthoma elasticum in β thalassemia and the sickling syndromes

Abstract: The development of clinical and histopathologic manifestations of a diffuse elastic tissue defect, resembling inherited pseudoxanthoma elasticum (PXE), has been encountered with a notable frequency in patients with ␤ thalassemia, sickle cell disease, and sickle thalassemia. The PXE-like clinical syndrome, consisting of skin, ocular, and vascular manifestations, has a variable severity in these hemoglobinopathies and it is age-dependent, with a generally late onset, after the second decade of life. The defect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
125
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 82 publications
4
125
0
6
Order By: Relevance
“…Indeed, the mean cardiac index was nearly 5 l/ min per square meter, being significantly higher compared to controls. Besides chronic anemia, the frequently coexistent hepatic involvement [20] as well as the recently described pseudoxanthoma-elasticum-like diffuse elastic tissue [21][22][23][24][25], which probably renders vessels more susceptible to dilatation by pulse pressure increase in the context of a hyperkinetic state, may both play a role [7,[20][21][22][23][24][25]. However, it has been shown that LV function copes quite well with chronically increased cardiac output [26] whereas there was no correlation between hemoglobin or cardiac output levels with LV ejection fraction or tissue Doppler systolic indices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the mean cardiac index was nearly 5 l/ min per square meter, being significantly higher compared to controls. Besides chronic anemia, the frequently coexistent hepatic involvement [20] as well as the recently described pseudoxanthoma-elasticum-like diffuse elastic tissue [21][22][23][24][25], which probably renders vessels more susceptible to dilatation by pulse pressure increase in the context of a hyperkinetic state, may both play a role [7,[20][21][22][23][24][25]. However, it has been shown that LV function copes quite well with chronically increased cardiac output [26] whereas there was no correlation between hemoglobin or cardiac output levels with LV ejection fraction or tissue Doppler systolic indices.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced NO availability leads to a continuous process of vascular deregulation, consisting of increased in situ thrombogenicity, vasoconstriction, and, particularly in the case of sickling syndromes, increased erythrocyte adhesion, delayed transient time, and hence increased predisposition to sickling [39]. In parallel, the hemolysis-induced oxidative tissue damage has been related to the aforementioned diffuse elastic tissue defect [21][22][23], as pulmonary alveoli consist of a high concentration of elastic fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse elastic fiber defects, resembling those reported in inherited pseudoxanthoma elasticum, have also been detected in patients with ␤-thalassaemia and sickle cell anemia (30), and in other hemolytic anemias (31,32). The genetic basis for these diseases cannot be directly linked to any structural or regulatory components involved in elastic fiber production (30,33,34).…”
mentioning
confidence: 81%
“…The genetic basis for these diseases cannot be directly linked to any structural or regulatory components involved in elastic fiber production (30,33,34). However, it has been suggested that the accumulation of iron in these patients, resulting from hemolysis, increased iron absorption, and multiple blood transfusions may lead to acquired elastic tissue defects (30).…”
mentioning
confidence: 99%
“…This is particularly intriguing as there is a high incidence of PXE manifestations in Mediterranean patients with beta-thalassemia, sickle cell and sickle thalassemia. These diseases all derive from genetic lesions leading to an abnormal or reduced production of beta-globin whereas the PXE manifestations associated with the betathalassemias don't seem to derive from ABCC6 mutations [61]. Therefore, one could speculate that the ABCC6 expression may be influenced by altered NF-E2 binding in beta-thalassemia patients and a functional correlation could then be suggested between a detoxification function of ABCC6/Abcc6 and the hemoglobin/heme metabolism in liver.…”
Section: Discussionmentioning
confidence: 99%